2011
DOI: 10.1016/j.ejphar.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

PTD4-apoptin protein and dacarbazine show a synergistic antitumor effect on B16-F1 melanoma in vitro and in vivo

Abstract: PTD4-apoptin protein enters cells and harbors tumor-selective cell death activity. Dacarbazine is the mainstay of treatment for malignant melanoma. In this study, we investigated the cytotoxic effect of PTD4-apoptin protein and/or dacarbazine in mouse B16-F1 and human A875 and SK-MEL-5 melanoma cells in vitro and by means of a mouse B16-F1 melanoma model in vivo. PTD4-apoptin protein inhibits the growth of B16-F1, A875 and SK-MEL-5 melanoma cells in a dose-dependent manner, but not in normal human cell lines W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 26 publications
2
22
0
1
Order By: Relevance
“…Notably, whilst DTIC treatment (40 µM) did not induce apoptosis, combined pitavastatin-DTIC treatment resulted in significant levels of apoptosis as evidenced by the increased level of apoptosis markers, cleaved PARP and active caspase 3, as well as annexin V staining. The results of the present study are in agreement with a number of studies which demonstrate that high concentrations of DTIC are necessary to induce apoptosis in melanoma cells (19,32,36). Whilst there has been insufficient research to determine which type of apoptosis is induced by DTIC, sensitization to the intrinsic apoptotic pathway has been revealed to augment DTIC-induced melanoma tumour cell death (37).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Notably, whilst DTIC treatment (40 µM) did not induce apoptosis, combined pitavastatin-DTIC treatment resulted in significant levels of apoptosis as evidenced by the increased level of apoptosis markers, cleaved PARP and active caspase 3, as well as annexin V staining. The results of the present study are in agreement with a number of studies which demonstrate that high concentrations of DTIC are necessary to induce apoptosis in melanoma cells (19,32,36). Whilst there has been insufficient research to determine which type of apoptosis is induced by DTIC, sensitization to the intrinsic apoptotic pathway has been revealed to augment DTIC-induced melanoma tumour cell death (37).…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study provide several lines of evidence to suggest that pitavastatin may synergistically enhance the anti-cancer effects of DTIC. The half-maximal inhibitory concentration (IC 50 ) of DTIC in several melanoma cell lines, including A375, A875, SB2, MeWo, B16-F1 and SK-MEL-5, has been demonstrated to be relatively high at >100 µM (5,32). Similar results were also obtained from the present study, where the IC 50 of DTIC in the A375 and WM115 cell lines was >100 µM.…”
Section: Discussionsupporting
confidence: 79%
“…Although we hypothesized that the mechanism of action for these two different agents would create a synergistic response as others have seen using combinations of dacarbazine with unrelated agents (Jin, Gong et al 2011), in fact that is not what was observed. While unexpected, our results are similar to what others have also observed using BrP-LPA.…”
Section: Discussionmentioning
confidence: 48%
“…25,26 However, apoptin did not induce apoptosis in normal diploid human cells, because apoptin acts as a multimeric protein complex, and apoptin becomes selectively phosphorylated in tumor cells. 27 Based on the above properties, apoptin is expected to be a potential anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…25 Apoptin, a chicken anemia virus protein, can induce p53-independent, Bcl-2 insensitive apoptosis in various tumor cells, but not in normal human cells. 26 TUNEL assays were performed on HeLa tumor cells treated with apoptin or nanoparticles loading apoptin (Figure 7).…”
Section: Determination Of Induction Of Apoptosismentioning
confidence: 99%